Salidroside inhibits the proliferation and migration of gastric carcinoma cells and tumor growth via the activation of ERS-dependent autophagy and apoptosis. Issue 44 (15th August 2019) - Yan, Wei; Li, Kai; Buhe, Amin; Li, Tianxiong; Tian, Peirong; Hong, Jun
Abstract : The endoplasmic reticulum stress (ERS)-induced autophagy and apoptosis are favorable for the suppression of many cancer types. Abstract : The endoplasmic reticulum stress (ERS)-induced autophagy and apoptosis are favorable for the suppression of many cancer types. Salidroside (Salid) has been proven to be capable of inducing the apoptosis of many cancer cells. However, the underlying mechanisms and whether Salid can activate the autophagic system have still not been explained thoroughly. Herein, the inhibition effect of Salid on the growth and progress of gastric cancer and the underlying mechanisms were investigated. With the SGC-7901 cells acting as the cancer model cells, we ascertained that Salid exerted a superior antagonism effect on the growth and migration of gastric cancer cells in a dose-dependent manner. Additionally, Salid exhibited strong capacity to induce cell apoptosis by the down-regulation of proliferation-related genes (Ki67 and PCNA), increase in the pro-apoptotic protein C-caspase-3, and changing the levels of other related genes. A mechanism study revealed that the levels of the ERS-related genes, such as CHOP, C-caspase-12, GADD34, and BiP, in the SGC-7901 cells dramatically changed post-treatment by Salid, indicating the involvement of ERS in Salid-inducing cell apoptosis. In addition, the increased LC3 + autophagic vacuoles, enhanced conversion of LC3-I to LC3-II, and inhibition of the PI3K/Akt/mTOR pathway further confirmed the activation of autophagy induced by Salid. Importantly, the effect of Salid in regulating the levels of autophagy-related proteins or the signaling pathway could be markedly depressed by co-incubating with Wortmannin (Wort), an autophagy inhibitor. The final evaluation of the tumor therapy efficacy exhibited satisfactory cancer growth inhibition by Salid with negligible toxicity to normal tissues. In summary, the present work provides a comprehensive effective evaluation of Salid for treating gastric cancer. The detailed investigation of the underlying mechanisms may offer a rational reference for the future applications of Salid in clinic.